Student mobility - Recruitment to studies and supply of post-graduates in a geographical perspective - Lasse Sigbjørn Stambøl (European Regional Science Association (ERSA), 2013)
One important incentive for a regional, decentralised university- and college structure is that higher education institutions should supply the local labour markets with sufficient high-educated labour. Local and regional recruitment to studies is expected to increase the probability that post-graduates will stay in the regions after studies. The main aim of the paper is to investigate the function of the higher education institution due to the local, regional and national recruitment to high education and the local, regional and national distribution of the supply of post-graduates. The investigation is first based on the geographical recruitment to university and college graduation in the year of 2002 by the regional residential background of students defined by categories of regions by distance from the region of study. Second, the regional distribution of the supply of post-graduates is based on all students in the year of 2004 that were not in education in the year of 2005 and their regional settlement in the years of 2007 and 2010 measured relatively to their region of study. National average indicates a higher local supply of post-graduates compared with the local recruitment. Small deviation in the geographical distribution of post-graduates between the years of 2007 and 2010 indicates that regional adjustments among post-graduates mostly take place during their studies or just after their graduation. It is detected small gender deviation between the share of recruitment and supply of post-graduates within the regions of study, while the female percentage increases when extending the local area to cover the remaining local county. Furthermore, it is observed higher local recruitment to studies and higher local supply of post-graduates among older than younger students. The local supply of post-graduates is higher among students finishing a short higher graduation compared with those obtaining a master or a doctoral degree. Business and administration, humanities and arts, education and health, welfare and sports are the fields of education that show the highest local recruitment, while the highest local supply of post-graduates is found in the fields of education of social science and low and humanities and arts, while health, welfare and sports and education increase their local importance when including the remaining local county as part of the local area. There are observed strong variations in local recruitment and local supply of post-graduates between the regional levels of centrality and between single regions within equal centralities indicating a heterogeneous local structure of recruitment to studies and supply of post-graduates across regions even when controlling for the fields of education structure. The most central regions show, however, higher local supply of post-graduates than the local recruitment to studies suggest.
Keywords: I2; J1; J22; J61; 330; Regional student mobility; High education; Recruitment to studies; Regional distribution of post-graduates